Technology-Based Accounting Implementation: A Case Study of P2MW Student Entrepreneurs - Warda, Nabila; Ramayanti, Rizka (Universitas Sains dan Teknologi Komputer, 2025)
The rapid advancement of information technology has significantly transformed accounting practices, including among student entrepreneurs. This study aims to analyze the implementation of technology-based accounting among participants of the Student Entrepreneur Development Program (P2MW) using the Technology Acceptance Model (TAM) and Technology Readiness Index (TRI) frameworks. A descriptive qualitative method with a case study approach was applied to ten informants through in-depth interviews and Likert-scale questionnaires, analyzed thematically and supported by TRI score interpretation across the dimensions of optimism, innovativeness, discomfort, and insecurity. The findings reveal that technology acceptance in accounting is influenced by perceived usefulness, which includes time and cost efficiency, improved data accuracy, ease of real-time access, and accelerated strategic decision-making, as well as perceived ease of use that minimizes technical barriers. The TRI analysis indicates high levels of optimism and innovativeness, with low discomfort and insecurity, reflecting strong readiness for technology adoption. The study concludes that implementing technology-based accounting among student entrepreneurs provides tangible benefits and encourages sustainable use, with practical implications for application developers, educational institutions, and policymakers in strengthening accounting technology literacy among young entrepreneurs